Effektiv närvarodetektering och närvaroräkning för optimerad lokalanvändning - Asplund, Gustaf; Dahlström, Ella; Eriksson, Oscar; Hakeskog, Lilly; Nordin, Isak; Olsson, Hugo (My University)
This project involves creating a system for occupancy measurement and people counting. The system has been tested in group study rooms at Chalmers University of Technology. A customer survey has been conducted among Chalmers students. In the survey, they rated the difficulty of finding group study rooms and what technical solutions they are most comfortable with. In addition, they were asked what medium that they would prefere to receive data regarding availability of group study rooms. The project was carried out iteratively with two different testing periods using different sensors. An occupancy sensor was created containing a PIR sensor HC-SR301 and a radar unit Micradar R60AMP1. Since the Micradar radar unit could only measure up to two people in a room, a second prototype was developed using the same PIR sensor and another radar unit – MinewSemi MS72SF1. During the second testing period, up to 6 people could be counted in a group room using the radar unit but more have not been tested. The occupancy sensors were connected to a Raspberry Pi Pico W microprocessor with custom embedded software. A Raspberry Pi 3A was used to provide the microprocessors with wireless internet, and a housing was created using CAD and 3D printing to mount the sensors in the group rooms. A backend structure for data management and a web application that presents data from the group rooms were also created. The web application thus shows students which group rooms are available or in use, as well as displaying statistics on usage over time. The statistics gathered show that the radar sensors are superior to the PIR-sensor in people counting and occupancy measurement